Myeloid Sarcoma Developing in Prexisting Hydroxyurea-Induced Leg Ulcer in a Polycythemia Vera Patient - Hatim Nafil; Illias Tazi; Lahoucine Mahmal (Case Reports in Medicine, 2013)
Myeloid sarcoma (MS) is an extramedullary tumour consisting of myeloblasts or immature myeloid cells located in an extramedullary site. It may occur at presentation of AML, at relapse, or prior to the onset of frank leukemia. We report a rare case of MS developing in prexisting Hydroxyurea-induced leg Ulcer in a 70-year-old woman.